2015
DOI: 10.4103/1305-7456.163238
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-cadherin in normal oral mucosa, in oral precancerous lesions and in oral carcinomas

Abstract: Objective:The aim of the present study was to assess the expression of E-cad in oral precancerous lesions and conditions and oral carcinomas in comparison with normal mucosa.Materials and Methods:Total of 50 samples were selected for the study and were categorized into five groups and 10 samples in each group as Group I-oral leukoplakia (OL), Group II-oral lichen planus (OLP), Group III-oral submucous fibrosis (OSMF), Group IV-oral squamous cell carcinoma (OSCC) and Group V-normal oral mucosa (NOM) as control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 22 publications
8
48
0
1
Order By: Relevance
“…13 Many authors have suggested that low E-cadherin immunoexpression could indicate tumor progression in leukoplakia. 7,8,15,16 This finding is in line with Santos-García et al, 15 in which 20% of leukoplakias with epithelial dysplasia and 73% of carcinomas in situ and microinvasive carcinoma had poor E-cadherin expression. Our results corroborate those of previous studies, since we observed that the expression of E-cadherin is in agreement with the severity of epithelial changes observed in leukoplakia and dysplastic oral leukoplakia showed lower immunocytochemical expression of this molecule than non-dysplastic leukoplakia.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…13 Many authors have suggested that low E-cadherin immunoexpression could indicate tumor progression in leukoplakia. 7,8,15,16 This finding is in line with Santos-García et al, 15 in which 20% of leukoplakias with epithelial dysplasia and 73% of carcinomas in situ and microinvasive carcinoma had poor E-cadherin expression. Our results corroborate those of previous studies, since we observed that the expression of E-cadherin is in agreement with the severity of epithelial changes observed in leukoplakia and dysplastic oral leukoplakia showed lower immunocytochemical expression of this molecule than non-dysplastic leukoplakia.…”
Section: Resultssupporting
confidence: 80%
“…Some studies have indicated a reduction in the immunohistochemical expression of this molecule in early stages and during the progression of oral cancer. 7,8 Proteins involved in the terminal differentiation of keratinocytes, such as involucrin, have also been found to have a low expression in biopsy tissues in leukoplakia associated with epithelial dysplasia when compared with oral mucosal cells exposed or not to carcinogens. 9 The immunoexpression of these cell adhesion and differentiation markers has been investigated in different stages of carcinogenesis in biopsy tissues, but there are no studies on the expression of these proteins using cytopathological analysis of the oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadherin‐1 (E‐cadherin) is expressed in epithelial cells and is an important cell adhesion molecule. It plays a role in cell growth, differentiation, migration and polarity . Loss of E‐cadherin is a hallmark of EMT …”
Section: Introductionmentioning
confidence: 99%
“…A marcação de E-caderina na mucosa normal era forte e contínua, diferente do que foi observado nas células neoplásicas, onde a expressão era mais fraca e descontínua (Pereira et al, 2016;Sridevi et al, 2015). …”
Section: E-caderinaunclassified